Pyoderma Vegetans Associated with Ulcerative Colitis: A Case with Good Response to Steroids - Filiz Canpolat; Bengü Çevirgen Cemil; Demet Yılmazer; Okan Yeşilli; Fatma Eskioğlu (Karger Publishers, 2011)
Pyoderma vegetans (PV) is a very rare disorder characterized by erythematous, vesiculopustular, exudative, vegetating plaques usually localized in the inguinal and axillary folds. The etiology of PV is not known, but it is often associated with bacterial infections in immunocompromised patients. Major histopathological features in PV are pseudoepitheliomatous hyperplasia and intraepidermal and subepidermal neutrophilic or eosinophilic microabscesses. It is well known that these lesions are frequently associated with inflammatory bowel diseases, such as ulcerative colitis (UC) and Crohn's disease. No standardized treatment plan is available for PV, although antibiotic treatment has often been used, with variable results. The standard first-line therapy is still systemic steroids. Herein, we report a case of PV associated with UC with unusual localization that showed a good response to systemic corticosteroid, antibiotic and sulfasalazine therapy.